Sport-specific personality traits in national-level athletes: A comparative analysis - Sharma, M.; Kumar, P.; Senapati, S.; Bal, B. S.; Singh, P. (International Journal of Physiology, Exercise and Physical Education, 2025)
Aim: This study compares sport-specific personality traits (e.g., competitiveness in individual sports vs. team orientation in team sports) among national-level athletes. It analyzes how these traits differ across sport types and their impact on performance.